Abandoned to lust : sexual slander and ancient Christianity - Knust, Jennifer Wright, 1966- (Gender, theory, and religion., 2006)
Early Christians used charges of adultery, incest, and lascivious behavior to demonize their opponents, police insiders, resist pagan rulers, and define what it meant to be a Christian. Christians frequently claimed that they, and they alone were sexually virtuous, comparing themselves to those marked as outsiders, especially non-believers and ""heretics, "" who were said to be controlled by lust and unable to rein in their carnal desires. True or not, these charges allowed Christians to present themselves as different from and morally superior to those around them. Through caref